Two Ships Passing in the Night—But Shooting Up Flairs From Time to Time!. (January 2020) - Simonton, Dean Keith
Although this article's author and Ellen Winner completed their graduate training at Harvard's now extinct Department of Psychology and Social Relations in the 1970s, they pursued divergent paths that only intersected on a few critical occasions, especially two discomfiting events during scientific meetings (the first event for her and the second for the author). Yet these distressing events stimulated this author to produce new publications on two crucial issues: artistic talent and creative life cycles. He much later reciprocated by inviting her to contribute a chapter on child prodigies for his handbook on genius. Without ever having collaborated, a productive relationship still emerged, albeit almost entirely at a distance.